COMPUTER VISION SYNDROME: REVIEW AND METHODS FOR ASSESSMENT - Panayot N. Nikolov (Peytchinski Publishing, 2021)
Computer vision syndrome (CVS) is a combination of eye and vision problems associated with the use of digital devices. CVS affects the eyesight, visual comfort and occupational productivity of workers due to the different symptoms computer users and staff experience: ocular discomfort, headache, dry eye, blurred vision etc. Aim of the study: To assess the symptoms of CVS in a software company in Varna by subjective and objective tests and prescribe measures for prevention. Materials and methods: 40 participants-31 men and 9 women were distributed with a valid questionnaire regarding common symptoms of CVS. The group was tested with the Schirmer test to measure the tear film quantity. Participants have passed a medical exam by an ophthalmologist before the study. Results: - 11 or 27,5% of the participants in the questionnaire have reached score ≥6 - have CVS - 10 or 25 % of the participants in the Schirmer test have reached results < 5mm. in the tear strip - The gender distribution shows 3 women (33.33%) and 8(25.8%) of men have CVS by questionnaire study and 3(33.33%) of women and 7(22.6%) of men based on Schirmer test have dry eye as asymptom of CVS. Conclusion: The results of the study predispose to further evaluation and tracking of the symptoms of CVS among this occupational group. All of the participants are aware of Ordinance № 7 related to health and safety work conditions with VDT's and received information regarding the physiological work-rest regime. Occupational risk of CVS can be reduced with early diagnose, assessment and prevention of the symptoms.